Evaluation of a Residential Mental Health Recovery Service in North Queensland - Marion Heyeres; Irina Kinchin; Irina Kinchin; Elise Whatley; Lisa Brophy; Lisa Brophy; Jon Jago; Thomas Wintzloff; Steve Morton; Vinitta Mosby; Narayan Gopalkrishnan; Komla Tsey; et al. (Frontiers Media S.A., 2018)
BackgroundEvidence shows that subacute mental health recovery occurs best when a person remains active within the community and fulfils meaningful and satisfying roles of their choosing. Several residential care services that incorporate these values have been established in Australia and overseas.AimsThis study describes (a) the development of an evaluation framework for a new subacute residential mental health recovery service in regional Australia and (b) reports on the formative evaluation outcomes.MethodsContinuous quality improvement and participatory research approaches informed all stages of the development of the evaluation framework. A program logic was established and subsequently tested for practicability. The resultant logic utilizes the Scottish Recovery Indicator 2 (SRI 2) service development tool, Individual Recovery Plans (IRPs), and the impact assessment of the service on psychiatric inpatient admissions (reported separately).ResultsService strengths included a recovery-focused practice that identifies and addresses the basic needs of residents (consumers). The consumers of the service were encouraged to develop their own goals and self-manage their recovery plans. The staff of the service were identified as working effectively in the context of the recovery process; the staff were seen as supported and valued. Areas for improvement included more opportunities for self-management for residents and more feedback from residents and carers.